The Prolonging Frustration and Fear in Jennette McCurdy’s I’m Glad My Mom Died - Oktafiani, Adelia Putri; Pasopati, Rommel Utungga (PT. Gudang Pustaka Cendekia, 2024)
This article examines how the memoir I’m Glad My Mom Died by Jennette McCurdy portrays the characteristics of frustration and fear in the main character of this memoir. The study aims to understanding the concept of frustration and fear that have the mostly negative impact to the everyday life. The researchers use qualitative approach, focusing on the context and some subjective interpretations in detail. The analysis uncovers that Jennette, as the main character of this memoir felt the frustration and fear in her everyday life. The conclusion states that fear and frustration may come to someone that is being expected to do more perfect deeds in general.